2008
DOI: 10.1002/er.1388
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of hybrid photovoltaic thermal (PV/T)‐active solar still

Abstract: SUMMARYIn this paper a new self-sustainable hybrid photovoltaic thermal (PV/T)-integrated-active solar still has been designed and tested for composite climate at I.I.T. New Delhi (28832 0 N; 77812 0 E). The PV system is used to generate electricity to run the pump (60 W and 18 V) as well as thermal energy to heat the water in the collector. The proposed design of hybrid-active solar still can be used at any remote location because of its self-sustainability. The experiments were performed on the set-up for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…The PV system is used to generate electricity to run a pump as well as thermal energy to heat the water in the collector. The hybrid-active solar system gave more than 3.5 times yield than the passive solar still [4]. Other recent work has shown that a thermal-driven refrigeration system using a new sorbent-sorptive as the working pair has achieved lower generator, lower evaporator temperatures, and higher coefficient of performance [5].…”
Section: Introductionmentioning
confidence: 92%
“…The PV system is used to generate electricity to run a pump as well as thermal energy to heat the water in the collector. The hybrid-active solar system gave more than 3.5 times yield than the passive solar still [4]. Other recent work has shown that a thermal-driven refrigeration system using a new sorbent-sorptive as the working pair has achieved lower generator, lower evaporator temperatures, and higher coefficient of performance [5].…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, space and cost of installation of PV module separately from the system has been avoided. In this case, solar radiation is transmitted through non-packing area of PV module and finally absorbed by the blackened absorber [5].…”
Section: A Single Slope Passive Solar Stillmentioning
confidence: 99%
“…Shiv carried out an experimental study on an active solar still with integrated photovoltaics and reported an output 3.5 times higher than for a passive solar still [147]. Rahul et al (2010) did an experiment combining the flat plate collector and PV with an active still and also presented a mathematical model for the system [148].…”
Section: Photovoltaic-thermal Stillsmentioning
confidence: 99%